Obesity in young adults: The effectiveness of self-empowerment-based patient-centered care in students with obesity in primary services - Dian Kusuma Dewi (Indonesian Nutrition Association, 2022)
The case of obesity in children and adolescents has increased every year globally. In 2016, the BMI of women aged 20 years and over globally reached 24.8 (24.6-25), while that of men reached 24.5 (24.3-24.6). According to the RISKESDAS, the proportion of obesity measured as central obesity at the age of >15 years in Indonesia increased throughout 2007, 2013 and 2018 by 18.8%, 26.6% and 31%. RISKESDAS 2018 concluded that obesity in adulthood increased in 2013 compared to 2007, the trend of non-communicable diseases (PTM) namely diabetes mellitus and hypertension also increased. The Medical Check-Up which was held to the new students of University of Indonesia in 2017 found that there were 1817 new students that classified as obese from the total 7268 new students (38.6% were obese). 2018, it was found that 24% out of 7487 new students were obese. In 2019, there were 29% out of 8583 new students that classified as obese.